Pengaruh Innovation Capability, Export Marketing Strategy, Dan Export Market Orientation Terhadap Export Performance - Anjeli Dwi Syarafina; Agustina Fitrianingrum (Cattleya Darmaya Fortuna, 2025)
This study investigates the influence of innovation capability, export marketing strategy, and export market orientation on the export performance of furniture SMEs in Jepara Regency after the Covid-19 pandemic. The background of this research is the significant impact of the pandemic on the furniture sector, highlighting the need to enhance export performance through innovation, marketing strategies, and market orientation. The study involved 35 furniture SME owners who engaged in export activities in 2024, with the number of respondents determined using a census method. The research employs a quantitative approach to explain the relationships between variables, using questionnaire data for analysis and Partial Least Squares (PLS) analysis via Smart-PLS to examine the inter-variable relationships. The findings reveal that innovation capability, export marketing strategy, and export market orientation each have a positive and significant impact on export performance, both individually and simultaneously. In conclusion, these three variables are crucial for improving the export performance of furniture SMEs in Jepara to compete in the global market. These findings offer practical implications for SMEs to focus more on innovation and marketing strategies tailored to export market needs. It is hoped that this study will contribute positively to the development of furniture SMEs, enhance the country’s foreign exchange earnings, and provide valuable insights for readers.